Öffentliche Unternehmen in Deutschland. Eine Analyse von Mikrodaten der amtlichen Statistik. - Dietrich, Irina (Univ.-Verl., 2012)
Die Arbeit enthält eine statistische Analyse der Gesamtheit öffentlicher Unternehmen in Deutschland und ihrer wirtschaftlichen Lage. Es werden Methoden der beschreibenden Statistik und der Jahresabschlussanalyse mit Bilanzkennzahlen angewandt. Vor allem in den letzten zwanzig Jahren wurde die Entwicklung der Gesamtheit öffentlicher Unternehmen durch Wandelprozesse geprägt und von Diskussionen über ihre Leistungsfähigkeit begleitet. Die Dynamik der Gesamtheit öffentlicher Unternehmen zeigt sich v. a. an der Vielfalt ihrer Aufgabenbereiche und Organisationsformen. Daher wird versucht, zunächst eine Bestandsaufnahme des öffentlichen Unternehmensbereichs durchzuführen. Ein weiteres Ziel ist die Beschreibung der Wirtschaftslage öffentlicher Unternehmen im letzten Jahrzehnt, wobei ihre Leistungsfähigkeit in den Vordergrund gestellt wird. Die Leistungsfähigkeit öffentlicher Unternehmen nur über die betriebswirtschaftliche Effizienz zu messen, ist gewiss einseitig und nicht ausreichend. Diese lässt sich aber im Vergleich zur volkswirtschaftlichen oder sozialen Effizienz leichter operationalisieren: Die betriebswirtschaftlichen Effizienzkriterien können gut aus den Jahresabschlüssen abgeleitet werden. Dadurch wird auch ein Vergleich mit privaten Unternehmen in gewissen Grenzen möglich. Die Beschreibung der Wirtschaftslage öffentlicher Unternehmen wird als Analyse ihrer einzelnen Teillagen (Vermögens-, Finanz- und Ertragslage) strukturiert. Insgesamt unterstreicht die Analyse der Teillagen die enge Verflechtung zwischen öffentlichen Unternehmen und öffentlichen Haushalten.

This monograph deals with state-owned companies in Germany. The study focuses on a statistical analysis of all state-owned companies in Germany and their economic situation. Approximately 9,000 state-owned companies, with nearly 500 characteristical items surveyed for every company, comprise the database for this statistical analysis. The elements examined are firstly the entries of the annual balance sheets. In addition, there are the identifying characteristics, such as the type of industry, the legal form, or the operating location, in the databank. The analysis covers the period from 1998 to 2007. It s very tantalizing for a statistician to work with the statistics of the annual balance sheets of the state-owned companies in Germany because of the large volumes of data. Both the methods of the descriptive statistics and the financial statement analysis with the balance sheet ratios were applied in this study. Especially over the last twenty years, the changes in the economic sector have led to discussions about the potential performance of the companies. The population dynamics of the state-owned enterprises are seen in the variety of the types of their activities and services and new legal forms. Therefore, the first goal of this analysis was to take an inventory of the German state-owned companies. The second goal of this work was to describe the economic situation of the state-owned companies in the last decade, with the emphasis on their performance. To measure the performance of the state-owned companies using only the economic efficiency as criterion is insufficient. However, the economic efficiency is easy to operationalise compared to, for example, social efficiency, because the ratios of the economic efficiency can be easily derived from the annual balance sheets of the companies. Besides that, using the ratios of the economic efficiency makes the comparison between the state-owned companies and the private ones easier. The description of the economic situation of the state-owned companies is based on the analysis of their assets, as well as their financial and earning positions. Altogether, the analysis of different positions emphasized the interdependence between the state-owned companies and their owners (regional authorities). From the methodological point of view, this study tried to extend research in the field of the data-driven statistics, which has been a neglected topic at universities in the last years when compared to model-driven statistics.
State-owned companies in Germany. An analysis of microdata from official statistics.
Keywords: Gemeindeunternehmen; Öffentliches Unternehmen; Unternehmensform; Organisationsform; Wirtschaftssektor; Statistik; Bestandsaufnahme; Leistungsfähigkeit; Bilanz; Umsatz; Finanzen; Kennzahl; Jahresabschluss; Finanzlage; Wirtschaftslage